(untitled) (Research, Society and Development, 2020)
The article aims to analyze how the STS/STSE approach associated with the pesticide theme has been incorporated into the teaching of Chemistry in the perspective of meaningful learning, through bibliographic review. The applied methodology consists of reading and analyzing articles, whose approach involved the theme of pesticides articulated to the issue of teaching Chemistry from the perspective of STSE – Science, Technology, Society and Environment) and meaningful learning, in order to answer three inherent questions to the themes. As a result, it was found that the data obtained from the analysis of the articles demonstrate that the application of STSE in the teaching of Chemistry promoted the development of critical and reflective awareness of students regarding the influences on science and technology in society, although there is still a long way to go for the consolidation of contextualized teaching with a focus on STSE and meaningful learning, even because in the Brazilian scenario changes in education depend, above all, on investments in initial and continuing teacher training, to overcome the lack of preparation in the area of natural sciences, thus reflecting on the improvement and quality of teaching.